Effect of Plant Spacing on Growth, Seed Yield and Quality of Gypsophila (Gypsophila Paniculata L.) (Bangladesh Journal of Agricultural Research, 2023)
Spacing is significant for determining desired plant population to achieve higher yields. Appropriate plant spacing makes more efficient use of nutrient and light leading to faster canopy establishment resulted in reducing moisture evaporation and weed growth. Hence, an experiment was conducted at the open research field of Floriculture Division, Horticulture Research Centre, BARI, Gazipur during 2019-20 and 2020-21 to determine the suitable plant spacing for growth, yield attributes, yield and quality of gypsophila. The experiment consisted of six plantspacing’s viz. broadcast (farmer’s practice ), 20 cm × 05 cm, 20 cm × 10 cm, 20 cm × 15 cm, 30 cm × 05 cm and 30 cm × 10 cm.The experiment was arranged in a randomized complete block design with three replications.BARI Gypsophila-1 was used as a variety.The blanket doses of fertilizers were N:100 kgha-1, P:40 kg ha-1, K:60 kg ha-1, S:20 kg ha-1, Zn:3 kg ha-1and B:1.5 kg per hectare was applied in the form of urea, TSP, MoP, gypsum, zinc sulphate and boric acid, respectively. The results exhibited that the highest seed yield (1308 kg ha-1) was obtained from the wider spacing of 30 cm × 10 cm. The same plant spacingachieved higher yield increment (8.28%) over farmer’spractice. The performance of growth and yield parameters were found better in the spacing of 30 cm × 10 cm. Economic analysis revealed that the highest gross margin and benefit cost ratio (2.21) wereachieved under the spacing of 30 cm × 10 cm.So, spacing 30 cm × 10 cm may be suitable for gypsophila cultivation but further research with wider spacing is needed for getting a conclusive result.Bangladesh J. Agril. Res. 47(2): 191-203, June 2022